Calorie shifting diet versus calorie restriction diet: A comparative clinical trial study - Sayed Hossein Davoodi (International Journal of Preventive Medicine, 2014)
Background: Finding new tolerable methods in weight loss has largely been an issue of interest for specialists. Present study compared a novel method of calorie shifting diet (CSD) with classic calorie restriction (CR) on weight loss in overweight and obese subjects. Methods: Seventy-four subjects (body mass index ≥25; 37) were randomized to 4 weeks control diet, 6 weeks CSD or CR diets, and 4 weeks follow-up period. CSD consisted of three phases each lasts for 2 weeks, 11 days calorie restriction which included four meals every day, and 4 h fasting between meals follow with 3 days self-selecting diet. CR subjects receive determined low calorie diet. Anthropometric and metabolic measures were assessed at different time points in the study. Results: Four weeks after treatment, significant weight, and fat loss started (6.02 and 5.15 kg) and continued for 1 month of follow-up (5.24 and 4.3 kg), which was correlated to the restricted energy intake (P < 0.05). During three CSD phases, resting metabolic rate tended to remain unchanged. The decrease in plasma glucose, total cholesterol, and triacylglycerol were greater among subjects on the CSD diet (P < 0.05). Feeling of hunger decreased and satisfaction increased among those on the CSD diet after 4 weeks (P < 0.05). Conclusions: The CSD diet was associated with a greater improvement in some anthropometric measures, Adherence was better among CSD subjects. Longer and larger studies are required to determine the long-term safety and efficacy of CSD diet.